The effect of tongue-tie incision on infant weight gain: a systematic review - Kadaristiana, Agustina; Nur Aini, Putri; Narendraswari, Prajnya Paramitha; Milenina, Nurul Syifa; Arifianto, Arifianto; Dwinanda, Novitria; Devy, Monica Sari (Paediatrica Indonesiana, 2026)
Background Tongue tie in breastfeeding infants may affect breast emptying, which may increase the likelihood of infant weight faltering. However, the benefits of tongue-tie incision on weight gain remain unclear. Objective To investigate the effect of tongue-tie incision on weight gain in breastfeeding infants by systematic review. Methods A systematic review was conducted by searching PubMed, Science Direct, EBSCO, Proquest, Wiley Online, the Cochrane Library, Scopus, and grey literature for published studies. Inclusion criteria for selecting articles were studies conducted on actively breastfed infants, articles with full texts, and randomized controlled trials, case-control studies, or cohort studies published within the last 10 years. The outcome assessed was weight gain. Risk of bias was assessed using the ROBINS-I V2 tools. Results Of the 382 articles screened, there were three pre-post cohort studies (one prospective and two retrospective) involving 419 infants who underwent tongue tie incision before the age of one year. No randomized controlled trials examined the effect of tongue-tie incision on weight gain. The studies reported an increase in weight gain and daily weight gain after tongue-tie incision. However, all studies had critical risks of bias due to a lack of controls and efforts to mitigate confounding risks. Conclusion There is insufficient evidence that tongue-tie incision could increase weight gain better than without incision.